Controlled and uncontrolled communication stimuli and organic food purchases: The mediating role of perceived communication clarity, perceived health benefits, and trust. Issue 2 (17th February 2019) - Anisimova, Tatiana; Mavondo, Felix; Weiss, Jan
Abstract: Despite a growing demand worldwide, organic food remains a niche category, with consumers only purchasing it some of the time. This study examines the mediating effects of consumers' perceived clarity of organic food-related communication, trust for, and perceived health benefits of organic foods in the relationship between controlled and uncontrolled communication stimuli and organic food purchases. We test our hypotheses on a sample of 1011 Australian organic food consumers using Structural Equation Modeling. We find that all mediators except perceived communication clarity perform as hypothesized, with the latter not mediating the relationship between uncontrolled communications and perceived health benefits of organic foods. The results suggest that marketers should ensure clarity in controlled organic food communications, signal health benefits of organic food and build consumer trust to generate organic purchases.